Analisis Jenis-Jenis Penelitian Pendidikan dan Aplikasinya pada Peningkatan Mutu Karya Ilmiah di Lembaga Pendidikan Islam - Ikhwan, Khairul; Hasdian, M Elhazri; Makarim, Nabil; Hidayatullah, Rully; Harmonedi, Harmonedi (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2025)
Educational research plays an important role in the development of educational science and practice, especially in Islamic educational institutions, as an alternative solution to the reliance on experience and intuition, which tend to be subjective and biased. This article aims to analyze the types of educational research and their characteristics, and discuss their relevance in the preparation of quality scientific work in the context of Islamic educational institutions. The method used is library research with a descriptive approach. The research shows that with a comprehensive understanding with the selection of qualitative, quantitative, mixed methods, and development research types must be adjusted to the objectives, context of the problem, and the needs of the analysis in order to produce relevant and in-depth scientific work in the environment of Islamic educational institution.